Method for preparing compact forsterite spinel composite material from magnesia tailings
By wet mixing and co-grinding of magnesite flotation tailings with tertiary bauxite and high-temperature sintering, dense forsterite-spinel composites are prepared, which solves the problems of low tailings utilization rate and environmental pressure, and achieves the realization of Efficient and low-cost resource recycling and material performance improvement.
Patent Information
- Application Number
- CN202411119564.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-13
AI Technical Summary
The existing technology is difficult to effectively utilize flotation tailings, resulting in waste of magnesite resources and environmental pressure, and traditional processes require pretreatment of tailings, which increases cost and complexity.
Wet mix and co-grind the magnesite flotation tailings with third-grade raw alumina, and then filtration, drying, pressing molding and high-temperature sintering, dense forsterite-spinite composite material is prepared, and the tailings are directly used without the need to use them directly Pretreatment improves resource utilization and material performance.
The preparation of high-quality dense forsterite-spinel composite materials is achieved, which solves tailings accumulation and environmental pressure, reduces production costs, and is simple and easy to produce on a large scale.
Smart Images

Figure CN119118642A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flotation tailings utilization, and in particular to a method for preparing a dense forsterite-spinel composite material by utilizing magnesia tailings. Background Art
[0002] With the large-scale mining of magnesite over the years, high-grade ore sources are becoming increasingly exhausted. In addition, the state has strengthened its control over the development of mining resources in recent years. High-grade magnesite has been difficult to meet the demand for the preparation of high-quality magnesium refractory materials. Currently, more and more companies have begun to use flotation technology to improve the purity of magnesium oxide (MgO) in magnesite. However, the flotation process will produce a large amount of 40%-50% flotation tailings, with MgO content of 35%-45%, SiO 2 The content is 20%-30%, and the burning reduction is about 25-35%.
[0003] Forsterite has the advantages of high melting point, low thermal expansion coefficient and good chemical stability, and is an excellent alkaline refractory material. 2 O 3 The only intermediate compound in the binary system, it has good erosion resistance, corrosion, peeling ability, good slag resistance, abrasion resistance, good thermal shock stability, high temperature resistance and other performance characteristics. It is an ideal raw material for the production of magnesia-alumina spinel bricks, ladle lining bricks, ladle castables and other refractory products for high temperature zone of cement rotary kiln. This technology makes full use of the main components of flotation tailings, MgO, SiO 2 , and the tertiary raw bauxite is used to prepare a dense forsterite-spinel composite material. The dense forsterite-spinel composite material can be used as a heavy raw material and can be used in the working lining of a high-temperature kiln below 1500°C. On the basis of preserving the low thermal conductivity and excellent alkali corrosion resistance of olivine itself, it improves the wear resistance and corrosion resistance of the material and prolongs its service life. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a dense forsterite-spinel composite material by utilizing magnesia tailings.
[0005] In the first aspect, the present invention provides a method for preparing a dense forsterite-spinel composite material using magnesia tailings, comprising: wet-mixing and grinding magnesite flotation tailings and tertiary raw alumina to obtain a mixture; filtering, drying, pressing, secondary drying and high-temperature sintering the mixture to obtain a dense forsterite-spinel composite material. The raw material of magnesia tailings used in the present invention is magnesite flotation tailings, and the characteristics of magnesite flotation tailings being rich in magnesium oxide and silicon oxide are utilized. The tailings raw material and tertiary raw alumina are mixed and wet-mixed and ground. Then filtering, drying, pressing, secondary drying and high-temperature sintering are performed to prepare a dense forsterite-spinel composite material.
[0006] Preferably, the mass ratio of the magnesite flotation tailings to the tertiary raw bauxite is 85-95:5-15. The present invention can prepare a high-quality dense forsterite spinel composite material by reasonably adjusting the tailings addition ratio.
[0007] Preferably, the wet mixing and grinding comprises mixing the magnesite flotation tailings, the tertiary raw bauxite and water, and performing wet mixing and grinding by ball milling.
[0008] In the present invention, the magnesite flotation tailings do not need to be pretreated and can be directly wet-mixed and co-ground with other raw materials.
[0009] More preferably, the ball milling time is 0.5-4 h, preferably 2 h, and the rotation speed is 50-70 r / min, preferably 60 r / min.
[0010] Preferably, the filter pressing is to perform vacuum filtration on the wet mixed and ground mixture to discharge the water in the mixture.
[0011] Preferably, the drying is to dry the mixture after filter pressing at 110-150° C. for 2-6 hours until the moisture content is less than 4%.
[0012] More preferably, the compression molding is to hydraulically mold the dried mixture at 90-110 MPa.
[0013] More preferably, the secondary drying is to dry the formed bricks at 100-120° C. for 12-24 hours; preferably, the bricks are dried until the moisture content is less than 1.5%.
[0014] Further preferably, the calcination temperature of the high temperature sintering is 1400-1550°C, preferably 1450-1500°C; the calcination holding time is 3-8h, preferably 4-6h. The present invention allows the magnesium oxide and silicon oxide in the raw materials to fully react by subjecting the formed sample to high temperature sintering under certain conditions, thereby better preparing the forsterite-spinel composite material.
[0015] The present invention uses magnesia tailings as raw materials, wet-mixes and grinds magnesite tailings and tertiary raw alumina in a pre-proportioned ratio, and performs filter pressing, drying, compression molding, secondary drying and high-temperature sintering, and prepares a dense forsterite-spinel composite material through raw material and process optimization. The present invention can solve the problems of low mixing uniformity and poor performance of forsterite, and reduces the problem of pretreatment of tailings by utilizing the characteristics of wet-mixing and grinding that can evenly mix raw materials.
[0016] In a second aspect, the present invention provides a dense forsterite-spinel composite material prepared by the method for preparing a dense forsterite-spinel composite material using magnesia tailings, wherein the dense forsterite-spinel composite material has forsterite as a main crystal phase and spinel phase as a secondary crystal phase.
[0017] In the present invention, the content ratio is affected by the amount of tertiary raw alumina added in the raw materials, and the required ratio can be achieved through blending.
[0018] The method for preparing a dense forsterite-spinel composite material using magnesia tailings provided by the present invention provides a way to explore the high-value utilization of flotation tailings, and can be produced on a large scale. According to the physical and chemical properties of the flotation magnesia tailings, magnesite, especially low-grade magnesite tailings, is recycled and utilized, which is not only of great significance for improving the environment and achieving zero discharge of magnesite resources, but also for further reducing the production cost in the application field.
[0019] The beneficial effects of the present invention are at least: 1) The method of the present invention directly preparing a dense forsterite-spinel composite material by using flotation tailings solves the restriction that the flotation tailings need to be pretreated in the traditional technology and improves the utilization rate of magnesite resources.
[0020] 2) The present invention alleviates the accumulation pressure of magnesite tailings, relieves environmental pressure, and promotes the green circulation and efficient utilization of secondary resources.
[0021] 3) The tailings used in the present invention are low in cost, and the operation process of using the tailings to prepare forsterite is simple, and it is easy to achieve large-scale production.
[0022] 4) The present invention provides a tailings treatment process, which effectively solves the problem of uneven and unstable tailings composition, and the obtained forsterite-based raw materials have stable performance and reliable quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 A process flow chart provided for an embodiment of the present invention.
[0025] Figure 2 XRD spectra of different formulations at a sintering temperature of 1450° C. provided in Example 2 of the present invention.
[0026] Figure 3The morphological characteristics of the sample at different magnifications at 1500° C. provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The composition of the magnesite tailings and tertiary raw bauxite used in the embodiments of the present invention is shown in Table 1.
[0029] Table 1 Composition of magnesite tailings and tertiary raw bauxite
[0030] Example 1
[0031] The embodiment of the present invention provides a method for preparing a dense forsterite spinel composite material by using magnesite flotation tailings, such as Figure 1 As shown, the specific operations are as follows.
[0032] Weighing: Weigh the magnesite flotation tailings and tertiary raw bauxite required for the sample, wherein the mass ratio of the magnesite flotation tailings and tertiary raw bauxite is 94:6.
[0033] Mixing: Place the raw materials in a ball mill, add water until appropriate, and ball mill at a speed of 60r / min for 2 hours to form a uniformly mixed raw material.
[0034] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0035] Drying: Dry the formed raw materials in a drying kiln at 110°C for 2 hours until the moisture content is less than 4%.
[0036] Molding: The filtered raw materials are pressed and molded on a hydraulic press at 100MPa.
[0037] Secondary drying: Dry the formed sample in a drying kiln at 110°C for 12 hours until the moisture content is less than 1.5%.
[0038] Sintering: Place the formed sample in a high-temperature box-type resistance furnace, first increase the temperature to 200°C at a heating rate of 5°C / min, then increase the temperature to 1500°C at a heating rate of 10°C / min, and keep it at that temperature for 4 hours. Cool it in the furnace to obtain the final product.
[0039] After testing, the performance indicators of the forsterite-spinel composite material prepared in this embodiment are: volume density 2.69g / cm 3 , water absorption rate 1.80%. Figure 3 This is the microstructure diagram of Example 1. It can be seen from the figure that the forsterite is tightly combined, and particles of different shapes and sizes are clearly visible, with distinct edges and relatively uniform distribution.
[0040] Example 2
[0041] A method for preparing a dense forsterite-spinel composite material by utilizing magnesite flotation tailings, wherein the specific operation is as follows.
[0042] Weighing: weigh the magnesite flotation tailings and tertiary raw bauxite required for the sample, wherein the mass ratio of the magnesite flotation tailings and tertiary raw bauxite is 91:9.
[0043] Mixing: Place the raw materials in a ball mill, add water until appropriate, and ball mill at a speed of 60r / min for 2 hours to form a uniformly mixed raw material.
[0044] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0045] Drying: Dry the formed raw materials in a drying kiln at 110°C for 3 hours until the moisture content is less than 4%.
[0046] Molding: The filtered raw materials are pressed and molded on a hydraulic press at 100MPa.
[0047] Secondary drying: Dry the formed sample in a drying kiln at 110°C for 15 hours until the moisture content is less than 1.5%.
[0048] Sintering: Place the dried sample in a high-temperature box-type resistance furnace, first increase the temperature to 200°C at a heating rate of 5°C / min, then increase the temperature to 1450°C at a heating rate of 10°C / min, and keep it warm for 4 hours. Cool it in the furnace to obtain the final product.
[0049] After testing, the performance index of the dense forsterite-spinel composite material prepared in this embodiment is: volume density 2.68g / cm 3 , water absorption rate 1.3%. Figure 2 As shown, its XRD spectrum shows that its main phases are forsterite and spinel.
[0050] Example 3
[0051] A method for preparing a dense forsterite-spinel composite material by utilizing magnesite flotation tailings, wherein the specific operation is as follows.
[0052] Weighing: weigh the magnesite flotation tailings and tertiary raw bauxite required for the sample, wherein the mass ratio of the magnesite flotation tailings and the tertiary raw bauxite is 88:12.
[0053] Mixing: Place the raw materials in a ball mill, add water until appropriate, and ball mill at a speed of 60r / min for 2 hours to form a uniformly mixed raw material.
[0054] Filter pressing: The mixed raw materials are introduced into the filter press for vacuum filtration. Excess water is squeezed out to obtain semi-dry uniform raw materials.
[0055] Drying: Dry the formed raw materials in a drying kiln at 120°C for 2 hours until the moisture content is less than 4%.
[0056] Molding: The filtered raw materials are pressed and molded on a hydraulic press at 100MPa.
[0057] Secondary drying: Dry the formed sample in a drying kiln at 110°C for 24 hours until the moisture content is less than 1.5%.
[0058] Sintering: Place the dried sample in a high-temperature box-type resistance furnace, first increase the temperature to 200°C at a heating rate of 5°C / min, then increase the temperature to 1400°C at a heating rate of 10°C / min, and keep it at that temperature for 3 hours. Cool it in the furnace to obtain the final product.
[0059] After testing, the performance index of the dense forsterite spinel composite material prepared in this embodiment is: volume density 2.65g / cm 3 , water absorption rate is 1.62%. Through the detailed description of the above embodiments, the method of the present invention can play an important role in the field of refractory materials and promote the green and sustainable development of the industry.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a dense forsterite-spinel composite material using magnesia tailings, characterized in that: include: The magnesite flotation tailings and the tertiary raw bauxite are wet-mixed and co-grinded to obtain a mixture; the mixture is subjected to filter pressing, drying, compression molding, secondary drying and high-temperature sintering to obtain a dense forsterite spinel composite material.
2. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to claim 1, characterized in that: The mass ratio of the magnesite flotation tailings to the tertiary raw bauxite is 85-95:5-15.
3. The method for preparing a dense forsterite spinel composite material using magnesia tailings according to claim 1 or 2, characterized in that: The wet mixing and grinding comprises mixing the magnesite flotation tailings, the tertiary raw bauxite and water, and performing wet mixing and grinding by ball milling.
4. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to claim 3, characterized in that: The ball milling time is 0.5-4h, and the rotation speed is 50-70r / min.
5. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to any one of claims 1 to 4, characterized in that: The filter press is to perform vacuum filtration on the wet mixed and ground mixture to discharge the water in the mixture.
6. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to any one of claims 1 to 5, characterized in that: The drying step is to dry the mixture after filter pressing at 110-150° C. for 2-6 hours.
7. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to any one of claims 1 to 6, characterized in that: The compression molding is to hydraulically mold the dried mixed material at 90-110 MPa.
8. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to any one of claims 1 to 7, characterized in that: The secondary drying is to dry the formed bricks at 100-120° C. for 12-24 hours.
9. The method for preparing a dense forsterite-spinel composite material using magnesia tailings according to any one of claims 1 to 8, characterized in that: The calcination temperature of the high-temperature sintering is 1400-1550° C., and the calcination holding time is 3-8 hours.
10. A dense forsterite-spinel composite material prepared by the method for preparing a dense forsterite-spinel composite material from magnesia tailings according to any one of claims 1 to 9; preferably, the dense forsterite-spinel composite material has forsterite as a main crystalline phase and spinel phase as a secondary crystalline phase.
Citation Information
Patent Citations
Method utilizing industrial slag to prepare magnesium aluminate spinel material
CN103936433A
Preparation method of magnesia-alumina spinel raw material
CN108585824A
Method for synthetising magnesium aluminium spinel
CN1086799A
Method for preparing forsterite and magnesia by sintering fine granular magnesite flotation tailings
CN115231580A
Mg-Al light thermal-insulated fireproof materials and method for preparing same
CN1704383A
Cited By
Periclase and forsterite composite material as well as preparation method and application thereof
CN119371219A
Forsterite-magnesium aluminate spinel refractory brick and preparation method thereof
CN121470971A
